Growth And Productivity Of Groundnut (Arachis Hypogaea) Under Different Tillage And Sowing Methods In India (Applied Biological Research, 2014)
A field experiment was conducted during rabi seasons of 2009-10, 2010-11  and 2011-12 to assess the effect of 3 tillage practices (conventional tillage, no  tillage and rotavator tillage) and 4 sowing methods (conventional sowing,  seed-cum-fertilizer drill sowing, paired row sowing and criss-cross sowing)  on groundnut production. Tillage methods showed no significant difference  in pod yield with maximum yield in rotavator tillage treatment (1570 kg ha-1).  Amongst the sowing methods, paired row sowing gave significantly highest  pod yield and net returns (1781 kg ha-1and 19730 ha-1, respectively). The interactionbetween tillage practices and sowing methods was non-significant. The study revealed that none of tillage practice effectively enhanced yield,  however paired row sowing proved superior in pod yield with 15.6, 22.2 and  25.4% increase over seed-cum-fertilizer drill, criss-cross sowing and  conventional sowing methods, respectively. Paired row sowing also  improved various yield associated attributes viz., number of pegs (35.1) and  pod plant-1(27.6), shelling percentage (66.6) and 100-kernel weight (33.6 g), and profitability ( 19,730) in groundnut.
Keywords: Groundnut; planting methods; pod yield; productivity; tillage